2008
DOI: 10.1109/aswec.2008.4483212
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study into Use of Dependency Injection in Java

Abstract: Over the years many guidelines have been offered as to how to achieve good quality designs. We would like to be able to determine to what degree these guidelines actually help. To do that, we need to be able to determine when the guidelines have been followed. This is often difficult as the guidelines are often presented as heuristics or otherwise not completely specified. Nevertheless, we believe it is important to gather quantitative data on the effectiveness of design guidelines wherever possible.In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…To our best knowledge, there is no commonly accepted definition of dependency injection in literature. Although all the authors [8], [23], [14] agree that its underlying idea is simple, the definitions they give are explanatory, and can be restated as Dependency injection means providing an object with its instance variables by an external entity.…”
Section: Dependency Injectionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our best knowledge, there is no commonly accepted definition of dependency injection in literature. Although all the authors [8], [23], [14] agree that its underlying idea is simple, the definitions they give are explanatory, and can be restated as Dependency injection means providing an object with its instance variables by an external entity.…”
Section: Dependency Injectionmentioning
confidence: 99%
“…After completing the analysis of 20 open source projects, the authors have found no apparent correlation between the use of dependency injection and coupling and cohesion metrics. The authors of [23] provide a classification of four different kinds of dependency injection: constructor and method (setter) dependency injection with and without default implementation of an injected object.…”
Section: Related Work and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [YTM08] empirically studied the prevalence of its use, and Razina and Janzen [RJ07] studied its impact on maintainability measures such as coupling and cohesion. DI has also been shown to be effective for configuring game components [PSC + 10] and connected with aspect-oriented programming [CI05], but there does not seem to be much other published research on dependency injection since Fowler [Fow04] provided its modern formulation.…”
Section: Related Workmentioning
confidence: 99%
“…In the last twenty years, dependency injection (DI) [Fow04,YTM08] has gained prominence as a design pattern for organizing the components of such a system, particularly in object-oriented programming environments.…”
Section: Introductionmentioning
confidence: 99%